COMMENTS ON GUIDELINES ON DIABETES, PRE-DIABETES, AND CARDIOVASCULAR DISEASES ESC-EASD 2007 - M. V. Shestakova (Рациональная фармакотерапия в кардиологии)
Comments on Guidelines on diabetes, pre-diabetes, and cardiovascular diseases ESC-EASD 2007.